2005
DOI: 10.14310/horm.2002.11162
|View full text |Cite
|
Sign up to set email alerts
|

A unique case of a benign adrenocortical tumor with triple secretion of cortisol, androgens, and aldosterone. Development of multiple sclerosis after surgical removal of the tumor

Abstract: We present a 39-year old female with a benign adrenal tumor characterized by autonomous secretion of cortisol, androgens, and aldosterone. The patient presented with a 4-year history of hypertension and severe hirsutism. Baseline investigations revealed elevated testosterone, androstendione, and 17OH progesterone with normal levels of dehydroepi androsterone sulfate. CT of the adrenals revealed a 2.5x3.0 cm tumor with characteristics of an adenoma on the left adrenal gland. Pelvic ultrasound was normal. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…We identified 11 cases of neurological disorders, including idiopathic intracranial hypertension (IIH) ( n = 5) [ 15 , 16 , 41 , 42 , 43 ], multiple sclerosis ( n = 2) [ 44 , 45 ], lymphocytic hypophysitis ( n = 2) [ 46 , 47 ], acute disseminated encephalomyelitis ( n = 1) [ 48 ] and myasthenia gravis ( n = 1) [ 49 ]. IIH has been associated with both primary adrenal insufficiency and steroid withdrawal [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…We identified 11 cases of neurological disorders, including idiopathic intracranial hypertension (IIH) ( n = 5) [ 15 , 16 , 41 , 42 , 43 ], multiple sclerosis ( n = 2) [ 44 , 45 ], lymphocytic hypophysitis ( n = 2) [ 46 , 47 ], acute disseminated encephalomyelitis ( n = 1) [ 48 ] and myasthenia gravis ( n = 1) [ 49 ]. IIH has been associated with both primary adrenal insufficiency and steroid withdrawal [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, Kamenicky et al showed that even benign cortisol-secreting adenomas are able to secrete normal to low normal levels of androgens which typically do not cause virilization ( 11 ). There are rare case reports of adenomas that cause both Cushing disease and virilization ( 13-18 ).…”
Section: Discussionmentioning
confidence: 99%
“…This tumour, in contrast to our case, also produced cortisol. 11 Immunohistochemical investigation revealed that the adenoma stained positive not only for CYP11B2 but also for CYP11B1. This costaining has been found in only 6% of patients with PA caused by ATPase or CACNA1D mutations compared to 49% and 45% in patients with a KCNJ5 mutant or wild-type tumour, respectively.…”
Section: A Pedunculated Aldosterone-producing Adenoma Drained By An Ementioning
confidence: 98%